2020
DOI: 10.1002/pen.25371
|View full text |Cite
|
Sign up to set email alerts
|

Improvement on properties of Chinese lacquer by polyamidoamine

Abstract: In this study, polyamidoamine (PAMAM) was added to raw lacquer in different proportions, and the curing process and properties of lacquer film were investigated by using thermogravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT‐IR), and scanning electron microscopy (SEM). To investigate the cross‐linking state between PAMAM and urushiol, NMR was used in this study. The experiments revealed that the comprehensive mechanical properties of modified‐film, especially the impact strength, were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Urushiol, a long‐chain hydrocarbon phenol from lacquer sap, is a mixture of 3‐alkyl‐substituted catechol derivatives with n = 15 linear carbon chains containing 0–3 olefins, together with other minor phenolic liquids, such as those having n = 17 carbon chains. [ 25‐28 ] Scheme 1 shows a typical structure of urushiol. [ 25 ] The compound is obtained through the extraction of lacquer sap from the trees Rhus vernicifera (China, Korea, and Japan), Rhus succedanea (North Vietnam and Formosa), and Melanorrhoea usitate (Thailand and Burma).…”
Section: Introductionmentioning
confidence: 99%
“…Urushiol, a long‐chain hydrocarbon phenol from lacquer sap, is a mixture of 3‐alkyl‐substituted catechol derivatives with n = 15 linear carbon chains containing 0–3 olefins, together with other minor phenolic liquids, such as those having n = 17 carbon chains. [ 25‐28 ] Scheme 1 shows a typical structure of urushiol. [ 25 ] The compound is obtained through the extraction of lacquer sap from the trees Rhus vernicifera (China, Korea, and Japan), Rhus succedanea (North Vietnam and Formosa), and Melanorrhoea usitate (Thailand and Burma).…”
Section: Introductionmentioning
confidence: 99%
“…The natural lacquer membranes do not have discoloration, wrinkles, blisters, and chips. Moreover, the addition of 10-20% of IFR reinforces the adhesion of lacquer membranes and the IFR does not fall off from the matrices, which suggests that the incorporation of IFR improves the adhesion level of lacquer membranes [15].…”
Section: Chemical Corrosion Resistance Of Combustion Resistant Rl/ifr Filmsmentioning
confidence: 94%
“…Zhang et al incorporated different contents of dendritic polyamidoamine (PAMAM) with raw lacquer, examining the effects of PAMAM over the curing process and properties of raw lacquer films. The test results showed that the comprehensive performances of raw lacquer films were improved [15]. In addition, the cross-linking between PAMAM and urushiol also helped reduce the curing time and strengthen the alkali resistance for raw lacquer.…”
Section: Introductionmentioning
confidence: 98%
“…The enzyme-catalysed polymerisation of oriental lacquer sap collected from lacquer trees in Asia allows it to be used as an energy-saving and environmentally friendly coating material with antibacterial, antiseptic, waterproof, and chemically resistant actions [1] , [2] , [3] , [4] , [5] , [6] , [7] . The lacquer thin films ensure excellent physicochemical properties such as high thermal stability, superior durability, anti-corrosiveness, good adhesion, and high gloss [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%